2012
DOI: 10.1071/en11164
|View full text |Cite
|
Sign up to set email alerts
|

Arsenosugar phospholipids and arsenic hydrocarbons in two species of brown macroalgae

Abstract: Environmental context. Although organoarsenic compounds occur in marine organisms at high concentrations, the origin and role of these compounds is unknown. Arsenic-containing lipids (arsenolipids) are newly discovered compounds in fish. We identify a range of arsenolipids in algae and propose that algae are the origin of these unusual arsenic compounds in marine ecosystems.Abstract. Fourteen arsenolipids, including 11 new compounds, were identified and quantified in two species of brown algae, Wakame (Undaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 18 publications
4
130
1
6
Order By: Relevance
“…production of lipid-soluble As compounds for membrane lipid bilayers). Many marine algae have arsenolipids including phosphatidyldimethylarsinylribose (usually termed phosphatidylarsenosugar, an arsenoribosyl derivative of phosphatidyl glycerol and a derivative of Oxo-PO 4 ), [43][44][45] and the arsenolipids are speculated to be included in the lipid bilayer structures of the algal outer membrane. [44] If cyanobacteria produce similar arsenolipids, they may be located at the cell membrane or thylakoid membrane, as well as phosphatidyl glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…production of lipid-soluble As compounds for membrane lipid bilayers). Many marine algae have arsenolipids including phosphatidyldimethylarsinylribose (usually termed phosphatidylarsenosugar, an arsenoribosyl derivative of phosphatidyl glycerol and a derivative of Oxo-PO 4 ), [43][44][45] and the arsenolipids are speculated to be included in the lipid bilayer structures of the algal outer membrane. [44] If cyanobacteria produce similar arsenolipids, they may be located at the cell membrane or thylakoid membrane, as well as phosphatidyl glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Four AsHCs were identified here (Table 2); the main AsHC360 is commonly found both in fish and algae, whereas AsHC374 and AsHC388 (found in field-collected Ectocarpus and cultures) have only been identified before in algae. [11,12] The ten AsPLs identified here have been reported in previous studies (Table 2). 57 % AE 9 (n ¼ 3) for Elachista, 75 % AE 5 (n ¼ 6) for Ectocarpus from Reykjavík and 76 % AE 7 (n ¼ 6) for Ectocarpus from Aberdeen, Table 2 (detailed quantification for each species is given in Supplementary Tables S8-S12).…”
Section: Identificationmentioning
confidence: 81%
“…by using AsPLs to replace phospholipids. [11,13] Benson and coworkers [14] grew algal cultures in 74 As V and showed that the arsenate was taken up by the algae, where the first biotransformation intermediates were lipid-soluble As species, thought to be AsPL. The AsPLs might therefore be formed first where the arsenosugars (AsSugars) are subsequently a hydrolysed product of the AsPLs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 14 arsenolipids, including 11 new compounds, were identified and quantified in brown algae, wakame (Undaria pinnatifida) and hijiki (Hizikia fusiformis), by HPLC-MS and GC-MS [19]. Both algal species contained arsenosugarphospholipids as the major type of arsenolipid, and arsenic-hydrocarbons were also detected, especially in Hijiki, suggesting that algae are the possible origin of these arsenolipids in marine ecosystems.…”
Section: Speciation Of Asmentioning
confidence: 99%